2013
DOI: 10.1093/molehr/gat080
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, identification and sequence analysis of RNAs selected for very short or long poly A tail in immature bovine oocytes

Abstract: A major challenge in applying genomics to oocyte physiology is that many RNAs are present but will not be translated into proteins, making it difficult to draw conclusions from RNAseq and array data. Oocyte maturation and early embryo development rely on maternal storage of specific RNAs with a short poly(A) tail, which must be elongated for translation. To resolve the role of key genes during that period, we aimed to characterize both extremes of mRNA: deadenylated RNA and long polyA tails mRNA population in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 70 publications
4
31
0
Order By: Relevance
“…Anchored oligo(dT) primers were used in this study to create the sequencing libraries with the intent of determining the levels of polyadenylated transcripts, which could be considered active transcripts (available for immediate translation). Even though a short polyadenine tail (5À10 bp) has been shown to be sufficient for polyadenine-dependent reverse transcription (Graindorge et al, 2006), the length of the polyadenine tail influences the reverse transcriptase efficiency (Gohin et al, 2013), so changes in transcript abundance detected by anchored oligo(dT) priming may represent changes in transcript polyadenylation status.…”
Section: Discussionmentioning
confidence: 99%
“…Anchored oligo(dT) primers were used in this study to create the sequencing libraries with the intent of determining the levels of polyadenylated transcripts, which could be considered active transcripts (available for immediate translation). Even though a short polyadenine tail (5À10 bp) has been shown to be sufficient for polyadenine-dependent reverse transcription (Graindorge et al, 2006), the length of the polyadenine tail influences the reverse transcriptase efficiency (Gohin et al, 2013), so changes in transcript abundance detected by anchored oligo(dT) priming may represent changes in transcript polyadenylation status.…”
Section: Discussionmentioning
confidence: 99%
“…In embryos, short poly(A) tails are necessary to repress translation until the appropriate stage of development is reached [9]. In addition, short poly(A) tails appear to denote mRNAs that are critical for early development, and may be a way to regulate translation in a dose and time-dependent manner [107]. Thus poly(A) tail length control and development go hand in hand.…”
Section: Some Final Thoughts On the Dynamics Of Poly(a) Tail Sizementioning
confidence: 99%
“…The late translation of ATF2LA − is an intriguing observation that suggests the existence of cis ‐elements in its 3′UTR that suppress polyadenylation. An in silico analysis by Gohin et al () revealed that the MAPS motif appears in transcripts containing a CPE, and that consensus MAPS sites are enriched in deadenylated mRNAs in bovine oocytes. Furthermore, their analysis of the molecular anatomy of 3′UTRs of ATF1 and ATF2 showed that only the second transcript bears a consensus MAPS (Gohin et al, ), which supports the notion that a cis ‐based mechanism delayed GFP translation from ATF2LA− .…”
Section: Discussionmentioning
confidence: 99%
“…An in silico analysis by Gohin et al () revealed that the MAPS motif appears in transcripts containing a CPE, and that consensus MAPS sites are enriched in deadenylated mRNAs in bovine oocytes. Furthermore, their analysis of the molecular anatomy of 3′UTRs of ATF1 and ATF2 showed that only the second transcript bears a consensus MAPS (Gohin et al, ), which supports the notion that a cis ‐based mechanism delayed GFP translation from ATF2LA− . Therefore, the MAPS may constitute a regulatory mechanism of ATF2 transcripts with a long 3′UTR in early bovine development, delaying its translation until an opportune stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation